2016
DOI: 10.9734/irjpac/2016/27469
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Review of the Catalytic Progress of Polylactic Acid Formation through Ring Opening Polymerization

Abstract: The reported research work was a multi-disciplinary, collaborative effort. Author SPD is the lead researcher and author of this manuscript. A detailed literature review and information regarding the ROP of lactide in the literature was conducted by author SPD as part of his doctoral thesis. Authors SPD, VM, HAA, JLB and KB contributed to the development of detailed study for the state-of-the art in the field of chronological development in the field of PLA processing. The author's contributed equally for makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 85 publications
(139 reference statements)
0
20
0
Order By: Relevance
“…due to microwave irradiation. [28], [42][43][44][45][46][47][48][49][50][51] Microwave assisted ROP technology for LA is emerging as a new green viable technique to synthesise PLA due to its homogeneous heating along with high efficiency [43][44][45][46][47][48][49][50][51], [69]. Liu et al have initially reported on the microwave-irradiated polymerization of D,L-LA [45,46] ).…”
Section: Chronological Scientific Research Development In Pla Synthesmentioning
confidence: 99%
See 2 more Smart Citations
“…due to microwave irradiation. [28], [42][43][44][45][46][47][48][49][50][51] Microwave assisted ROP technology for LA is emerging as a new green viable technique to synthesise PLA due to its homogeneous heating along with high efficiency [43][44][45][46][47][48][49][50][51], [69]. Liu et al have initially reported on the microwave-irradiated polymerization of D,L-LA [45,46] ).…”
Section: Chronological Scientific Research Development In Pla Synthesmentioning
confidence: 99%
“…The market for common household consumable polymers including HIPP, PVC and PET along with biodegradable polymers has been approximately around 200,000 tons in 2005, of which 50% was PLA. The demand for industrial production of biodegradable polymers instead of conventional petrochemical polymers increases many folds due to the environmental (landfilled) issues related to the petrochemical-based polymers [2,28]. Additionally, the incorporation of PLA based nanocomposites emerges as a huge area of interest and demand in medical applications.…”
Section: Industrial Concern and Contribution Industrial Concern And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…were taken straight from the literature. 30 Dubey et al 29,30,33 covers mostly the details of research work related to mathematical modelling of ROP process of lactide in last 10 years or so. This mathematical model provided the isothermal curves that were implemented in Ludovic®.…”
Section: 30mentioning
confidence: 99%
“…[31][32][33] At present, commercial versions of this soware do not come with an option to simulate reactive extrusion, i.e. when a reaction happens during the extrusion process (within the extruder barrel).…”
Section: Modelling Of Rop Reaction Mechanism In Reactive Extrusionmentioning
confidence: 99%